Treating Aggression and Self-destructive Behaviors by Stimulating the Nucleus Accumbens: A Case Series - Harat, Marek; Kiec, Michał; Rudaś, Marcin; Birski, Marcin; Furtak, Jacek (Frontiers in Neurology, 2021)
Self-destructive and aggressive behaviors can have a significant impact on the quality of life of affected individuals and their carers. While deep brain stimulation (DBS) has been applied to the treatment of self-destructive and aggressive behaviors in isolated cases, clinical data on this treatment modality are still lacking. We therefore assessed responses to treatment with bilateral DBS of the nucleus accumbens in six patients with severe self-destructive and aggressive behaviors. Three patients had Tourette syndrome and three had other underlying predispositions including obsessive compulsive disorder, cerebral palsy, encephalitis, and epilepsy. Patients were followed up for between 2 and 7 years, and patients were assessed using the Modified Overt Aggression Scale (six patients) and the Buss-Perry Aggression Questionnaire (three patients able to complete the questionnaire on their own). DBS reduced self-destructive and aggressive behaviors by 30-100% and by an average of 74.5%. Patients with Tourette syndrome responded better to DBS and improved by 27.3% according to the Buss-Perry Aggression Questionnaire. These results suggest that nuclei accumbens stimulation may be an effective treatment for aggressive and self-destructive behaviors regardless of etiology.